KARAKTERISTIK FISIKOKIMIA TEPUNG KELADI SINABOI (Colocasia esculenta) - Fahroji; Viona Zulfia (SAGU, 2021)
Taro is one of main commodities in Rokan Hilir Regency, Riau Province. The Sinaboi taro is usually traded as fresh tubers. Processing of taro flour is an alternative to increase added value of taro. The purpose of this research was to study the physicochemical characteristics of fresh tuber and taro flour. Taro was obtained from Sinaboi District then transported to the Postharvest Laboratory of Riau Assessment Institute for Agricultural Technology (AIAT), Pekanbaru. Then taro was made flour. Both of fresh tuber dan flour were analyzed for their physicochemical characteristics. The results showed that sinaboi taro was grouped into 2 grades, namely large size (BB) has 959 g weight and small size (BK) has 501 g weight. Size of BB grade was 41% longer than BK grade. Taro tuber has moisture content 62.93%, ash 1.42%, total protein 2.30%, fat 0.09%, crude fiber 0.76%, reducing sugar 1.62%, starch 27.54%, amylose 6.85%, L* 86.37, a* 5.40, and b* 8.52. Taro flour has moisture content of 11.63%, ash 3.17%, total protein 5.73%, fat 0.27%, crude fiber 1.22%, reducing sugar 1.94%, starch 67.80%, amylose 14.92%, L* 83.17, a* 6.99, and b* 5.19.